Bangladesh : promise and performance - Jahan, Rounaq (Dhaka : University Press, 2000)
Contributed articles on Bangladesh's social, economic, and political developments during the past three decades.
Includes bibliographical references (pages [369]-377) and index.
Complimentary copy from BIED
Keywords: Bangladesh -- Politics and government -- 1971-; Bangladesh -- Economic conditions; Bangladesh -- Social conditions